From Christianity to Judaism : Story of Isaac Orobio de Castro. - Kaplan, Yosef (Littman Library of Jewish Civilization., 1989)
A biography of Isaac Orobio de Castro, a crypto-Jew from Portugal and one of the most prominent intellectual figures in the 17th century. This work sheds light on the life of a Jewish community of former Christians in Amsterdam and examines their dilemmas and attempts to create a new identity.